Cervicothoracic Fixation by Domino Connector in Cervicothoracic Junction Tuberculosis–A Case Report - Amin, Md. Rezaul; Haque, Moududul; Nath, Haradhan Dev; Hossain, ABM Manwar; Bari, Mohammad Shahnawaz (Indian Journal of Neurotrauma, 2020)
Cervicothoracic junction tuberculosis involves the C7 to D3 levels of the spine which constitutes 5% of all spinal tuberculosis. As the cervicothoracic junction is transitional zone and a weight-bearing area, the anatomical considerations for treatment of cervicothoracic junction is very difficult. We did a lateral mass screw for C5, 6, and 7 and pedicle screw of D3 and 4 levels, and connected cervical 3.5 mm rod with thoracic 5.5 mm rod using a domino connector. We gave antituberculosis therapy for 18 months. We followed-up the patient routinely and she significantly improved.
Keywords: cervicothoracic; dorsal; medical research council; magnetic resonance imaging; tuberculosis